Performances of the first and second generation composite breed resulting from crossing between local Sumatra sheep and hair sheep. - Subandriyo .; Bambang Setiadi; M Rangkuti; K Diwyanto; M Doloksaribu; Leo P Batubara; Endang Romjali; Simo Eliaser; Eko Handiwirawan (Indonesian Center for Animal Research and Development (ICARD), 1998)
Improving sheep productivity can be conducted by genetic improvement and improving environmental factors. Genetic improvement usually can be done by selection and creating composite or synthetic breed by crossbreeding. Composite breed created by crossbreeding between different breeds and followed by selection. The study of crossing between Sumatra sheep with fat-tail sheep from East Java, St . Croix hair sheep (US) and Barbados Blackbelly hair sheep has been carried out since 1986, and show that the crossbred are better in term of production and reproduction . In 1996/1997, the first generation (F1) of composite breed (KOM) has been created by crossing between Barbados Cross (BC) rams and St . Croix Cross (HC) ewes or reciprocally. The second generation (F2) of composite breed has been created by inter-se mating . However, F1-KOM and F2-KOM vary in their performances, therefore selection should be conducted. The results showed that birth weight and weaning weight of crossing between BC rams and HC ewes tended to be heavier than those of reciprocal crossing between HC rams and BC ewes, but the differences were not significant (P>0 .05) . Birth weight and weaning weight of crossing between BC rams with HC ewes and reciprocal cross were 2.48 _+ 0.70 kg (n=791), 12 .50 _+ 3 .26 kg (n=640) and 2.37 _+ 0.62 kg (n=147), 12 .29 _+ 3.30kg (n=122), respectively . Meanwhile, observations of inter-se mating of Fl-KOM showed that the weight at the first mating was 26 .7 _+ 3.82 kg (n=80), age of dam at the first lambing was 15 .7 _+ 1 .73 months (n=83), weight at post-partum was 29 .86 _+ 3 .30 kg, and litter size at the first parity was 1 .43 _+ 0.59 (n=83) . The mean of age at the first mating of KOM was around 10 .7 months. Mean of mating weight at the second parity was 28 .29 +_ 3 .51 kg (n=11), age of dam at the second lambing was 20.6 _+ 1 .99 month (n=11), post-partum weight was 26 .92 _+ 4.03 kg (n=11) and litter size was 1 .64 _+ 0.81 (n=11) . Weaning weight of Fl-KOM, F2-KOM, BC, HC and St. Croix (H) after adjusted by season, sex, age of dam and type of birth were significantly different among Fl-KOM with F2-KOM, BC, HC, and H. However, there were no significantly different among F2-KOM with BC and HC. The results of the study indicated that for improving selection respons, the corrections or adjustments of environmentally induced superiority (sex, type of birth and age of dam at lambing) for every genotype and certain generation should be conducted, in order to increase the rate of genetic improvement. Key words : Composite breed, first generation, second generation